Peningkatan Minat Baca Dan Kunjungan Perpustakaan Aneka Ilmu Melalui Program KKN Di Desa Bogor Baru - Syafitri, Alya Novia; Amanda, Kiki Rizki; Saragih, Rosa Sri Andari; Muhammad Ravie; Syafira Dwi Wulandari; Deo Surya Anjaya; Dival Satria Gunawan; Bilal Chairul Ahmad; Rustikawati (CV. ITTC INDONESIA, 2025)
Reading interest in rural communities is often hindered by limited access to books and a lack of engaging literacy programs. This study aims to quantitatively measure the increase in reading interest and visits to the